PENGARUH DISIPLIN DAN KOMPETENSI TERHADAP KINERJA GURU YANG DIMODERASI OLEH GAYA KEPEMIMPINAN (Studi Pada Guru SMP Negeri Di Kecamatan Batang Kabupaten Batang) - Sukiyanto, 12.52.02.0247; Susilowati, Yeye (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study is to examine and analyze the influence of discipline and competence on teacherâs performance moderated by leadership styles of Junior High School teachers inÂ  Batang District of BatangÂ  Regency. The research uses survey, questionnaires, observations,Â  interviews andÂ  documentation. The hypothesis of this study is 1). Discipline has positive and significant influence on the teacherâs performance. 2). Competence has positive and significant influenceÂ  on the teacherâs performance. 3). The style of leadershipÂ  has positive influenceÂ  on teacherâs performance. 4).The style of leadership moderates theÂ  influence on the teachers performance. 5). The style of the school leadership moderates the influence on the competence of the teachersâ performance. The result of the study shows : 1). The influence of discipline towards teacherâs performanceÂ  is significant. It means that the discipline influences towards teacherâs performance. 2). The influence of teacher competence towards teacherâs performance is positive and significant. It means that the higher of teacherâs competence, the higherÂ  teacherâs performance. 3). The style of school leadership towards teacherâs performance is positive and significant. It means that the school leadership towardsÂ  the teacherâs performance does not influence the teacherâs performance 4). The influence of discipline which is moderated by school leadership towards the teacherâs performance is negative and is not significant. It means that the school style does not moderate discipline toward the teachersâ performance. 5). The competence which is moderated by the school leadership style towards teacherâs performance does not have positive impact and is not significant . It meansÂ  that school leadership style does not moderate teacherâs competence towards the teacherâs performance. Keywords: Discipline, competence, on teacher performance, moderated, leadershipÂ  style